Linear Birefringence of the Central Human Cornea - Knighton, Robert W; Huang, Xiang-Run (Investigative ophthalmology & visual science, 2002)
To determine the polarization properties of the central cornea at perpendicular incidence in a normal human population on the assumption that the cornea behaves as a linear retarder. A corneal polarimeter provided a view of the fourth Purkinje image of a yellow (585 nm) light-emitting diode through crossed polarizers and a variable retarder. The Purkinje image was extinguished by adjusting the fast axis and retardance of the retarder to match the slow axis and double-pass retardance of the cornea. Both eyes of 73 normal subjects (49 women, 24 men; ages, 21-71 years) were measured. Correlations were expressed as Pearson's r. In most corneas the slow axis pointed nasally downward, with the peak of the axis distribution falling between 10 degrees and 20 degrees nasally downward. Double-pass corneal retardance varied widely (range, 0-250 nm); 80% of retardance values were uniformly distributed from 40 to 140 nm. Retardance was moderately correlated with axis (r approximately 0.5), such that weaker retardance was associated with axes that were more nasally downward. Corneal birefringence was well correlated between the two eyes of a subject in both axis (r = 0.77) and retardance (r = 0.75). The variation of corneal birefringence among individuals is substantial enough to produce large, uncontrolled differences in the polarization state of a measuring beam, differences that can introduce variability in newer technologies for ophthalmic diagnosis. The interocular similarity of corneal birefringence suggests deterministic control of corneal development.